Riga-Fede Disease Associated with Natal Teeth: Two Different Approaches in the Same Case - Luiz Evaristo Ricci Volpato; Cintia Aparecida Damo Simões; Flávio Simões; Priscila Alves Nespolo; Álvaro Henrique Borges (Hindawi Limited, 2015)
Natal teeth are those present in the oral cavity at the child's birth. These teeth can cause ulcers on the ventral surface of the tongue, lip, and the mother's breast characterizing the Riga-Fede Disease. The treatment depends on the tooth's mobility and the risk of aspiration or swallowing; whether it is supernumerary or regular primary teeth; whether it is causing interference in breastfeeding; breast and oral soft tissue injuries; and the general state of child's health. A 1-month-old female infant was diagnosed with two natal teeth and an ulcerated lesion on the ventral surface of the tongue, leading to the clinical diagnosis of Riga-Fede Disease. The treatment performed consisted of the maintenance of the natal tooth that showed no increased mobility, adding a small increment of glass ionomer cement to its incisal edge, and orientation for hygiene with saline solution. Due to the increased mobility of the other natal tooth, surgical removal was performed. There was regular monitoring of the patient and complete wound healing was observed after 15 days. The proposed treatment was successful and the patient is still in follow-up without recurrence of the lesion after one year.